The transmission of knowledge among learned Bosnian Muslims as recorded in the manuscripts of Mustafa Muhibbi, a qadi from Sarajevo - Paić-Vukić, Tatjana (2008)
The paper examines the transmission of knowledge among learned Muslims in Ottoman Bosnia in the corpus of Arabic-script manuscripts that belonged to Mustafa Muhibbi (d. in 1854), an educated qadi from Sarajevo. The study of sources such as ownership statements, indicators of the origin of certain quotations, and examples of textual compilations has led to conclusions concerning the dissemination of books and transmission of learning, both written and oral. The manuscripts have also revealed the virtual absence of evidence of direct contcts between the so-called high cultures of Muslims and non-Muslims of that period.
Projekt MZOS
ENG